Mewujudkan Nelayan Siaga: Sinergi APD dan Simulasi Darurat sebagai Strategi Perlindungan Diri di Laut - Astrid Pratiwi Rufaedah Amir; Jumhur Salam; M Anas (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
Occupational safety in the fisheries sector, particularly among traditional fishermen, remains frequently overlooked, thereby increasing the risk of work-related accidents at sea. In Kampung Beru Village, Galesong District, Takalar Regency, three occupational incidents have been recorded over the past two years, resulting in two fatalities. This community service initiative aimed to enhance fishermen’s knowledge, skills, and awareness of occupational safety through education on the use of personal protective equipment (PPE) and emergency response simulations. The activity employed a participatory method involving 53 fishermen, who underwent preliminary health screenings, received PPE education, were introduced to first aid kits, and participated in simulations of emergency conditions at sea, such as drowning, cardiac arrest, and hypothermia. The results indicated a significant increase in fishermen’s awareness and prioritization of safety, as evidenced by their commitment to equipping their vessels with PPE and first aid supplies. This program demonstrates that experiential learning is an effective approach in fostering a culture of safety within fishing communities.